1997
DOI: 10.1002/jor.1100150214
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental osteomyelitis by surgical debridement and the implantation of bioerodable, polyanhydride‐gentamicin beads

Abstract: Osteomyelitis was induced in the radius in 77 rabbits and confirmed by histological examination and culture. At 4 weeks, the wounds were debrided and the animals were treated with (a) fatty acid dimer-sebacic acid beads (a bioerodable composite) impregnated with 20% or (b) 10% gentamicin sulfate, (c) placebo beads and intramuscular gentamicin sulfate, (d) placebo beads alone, or (e) debridement only. After 4 weeks, eradication of infection was determined by histological examination and culture. Osteomyelitis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 31 publications
(24 reference statements)
3
46
2
4
Order By: Relevance
“…Locally delivered Gd-DTPA was visualized from all three vehicles but absent from all control depots at all time points, as expected based on in vitro elution data [23]. Our data for distribution of locally delivered Gd-DTPA in soft tissue are consistent with in vivo tissue delivery measured by Adams et al [1], Nelson et al [22], and Owen et al [24]; with MRI data for drug distribution from a local infusion in vitro by Raghavan et al [26]; and with the local distribution after infusion into brain tissue in vivo [4] (Table 2). Our data showing visualization of Gd-DTPA over time with an MRI are consistent with Astary et al [4] and Raghavan et al [26], who also showed that gadolinium distribution can be seen to change with time.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Locally delivered Gd-DTPA was visualized from all three vehicles but absent from all control depots at all time points, as expected based on in vitro elution data [23]. Our data for distribution of locally delivered Gd-DTPA in soft tissue are consistent with in vivo tissue delivery measured by Adams et al [1], Nelson et al [22], and Owen et al [24]; with MRI data for drug distribution from a local infusion in vitro by Raghavan et al [26]; and with the local distribution after infusion into brain tissue in vivo [4] (Table 2). Our data showing visualization of Gd-DTPA over time with an MRI are consistent with Astary et al [4] and Raghavan et al [26], who also showed that gadolinium distribution can be seen to change with time.…”
Section: Discussionsupporting
confidence: 89%
“…Although there are considerable data characterizing in vitro release [1, 2, 7, 9, 11, 14-16, 23, 29], there are few in vivo data reporting antimicrobial distribution after local delivery. Antimicrobial concentration has been measured in bone and soft tissue adjacent to a local delivery in animals [1,22,24]. Adams et al [1] measured antimicrobial concentration in fluid, soft tissue, and bone adjacent to antimicrobial PMMA beads in mongrel dogs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local delivery is expected to achieve levels above MBEC for several days. In vivo pilot data from quantitative MRI and in vivo tissue levels are consistent with levels from local delivery of 100 to 2000 lg/ mL lasting 5 days or more indicating the concentrations consistent with expected MBECs can be achieved from local delivery [12,15]. Although MBEC is the concentration that potentially will eradicate biofilm in 24 hours, it is not known if treatment duration longer than 24 hours would require the same antimicrobial concentration.…”
Section: Introductionmentioning
confidence: 62%